2018
DOI: 10.1002/ajmg.a.38638
|View full text |Cite
|
Sign up to set email alerts
|

Low serum fatty acid levels in pregnancies with fetal gastroschisis: A prospective study

Abstract: Fetal gastroschisis is a paraumbilical abdominal wall defect with herniation of abdominal organs. The underlying cause of the disease remains unknown; however, studies suggest that nutritional factors may play a role in its development. This prospective case-control study explored the association of serum fatty acid levels of pregnant women and occurrence of gastroschisis. Gastroschisis group comprised 57 pregnant women with fetuses with gastroschisis, and the control group comprised 114 pregnant women with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…For this methylation study, we used the mother-infant pairs from the previously described case-control study to investigate nutrition and other risk factors in gastroschisis. 8,28,29 The patients were treated, blood was drawn, and data were collected at the Departamento de Obstetrícia e Ginecologia do Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo between July 2013 and July 2015. Briefly, consenting singleton pregnant women at gestational age under 34 weeks and with isolated fetal gastroschisis were included in this study.…”
Section: Techniques and Materialsmentioning
confidence: 99%
“…For this methylation study, we used the mother-infant pairs from the previously described case-control study to investigate nutrition and other risk factors in gastroschisis. 8,28,29 The patients were treated, blood was drawn, and data were collected at the Departamento de Obstetrícia e Ginecologia do Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo between July 2013 and July 2015. Briefly, consenting singleton pregnant women at gestational age under 34 weeks and with isolated fetal gastroschisis were included in this study.…”
Section: Techniques and Materialsmentioning
confidence: 99%
“…In Case 2, the mother's gastroplasty may have contributed to a low absorption of nutrients during pregnancy. In a previous study by our group, pregnant women whose fetuses had gastroschisis consumed a great deal of calories but few essential amino acids, and they had low serum levels of essential fatty acids (Centofanti et al, 2018). However, we were unable to correlate these data with those of the methylation analysis of this study given the absence of a standard cutoff score for the nutrients.…”
Section: Discussionmentioning
confidence: 89%
“…The methylation profile was investigated as previously described (Freitas et al, 2021); the methylation array was performed for all samples (five study samples and 32 control samples), and the single nucleotide polymorphism (SNP) array was performed only for the two fetuses with gastroschisis. Major details about the study protocol were reported previously 1 (Centofanti et al, 2018; Centofanti et al, 2019; Freitas et al, 2021). The genomic positions were reported according to the Homo sapiens reference genome (hg19, Genome Reference Consortium GRCh37 build, Feb/2009).…”
Section: Methodsmentioning
confidence: 99%
“…The study was a secondary aim of a larger case-control study investigating the risk factors and nutritional status of pregnant women carrying a fetus with gastroschisis. 22,23 Pregnant women where the fetus was suspected to have gastroschisis were referred to the Fetal Medicine Unit at the Department of Obstetrics and Gynecology at Hospital das Clinicas, Sao Paulo University Medical School between July 1, 2013, and July 1, 2015. A detailed fetal anomaly scan was conducted to confirm fetal gastroschisis.…”
Section: Methodsmentioning
confidence: 99%